Weak Expression of Terminal Complement in Active Antibody-Mediated Rejection of the Kidney - Tiller, Gesa; Lammerts, Rosa G. M.; Karijosemito, Jessy J.; Alkaff, Firas F.; Diepstra, Arjan; Pol, Robert A.; Meter-Arkema, Anita H.; Seelen, Marc. A.; van den Heuvel, Marius C.; Hepkema, Bouke G.; Daha, Mohamed R.; van den Born, Jacob; et al. (Frontiers in Immunology, 2022)
Background The role of the complement system in antibody-mediated rejection (ABMR) is insufficiently understood. We aimed to investigate the role of local and systemic complement activation in active (aABMR). We quantified complement activation markers, C3, C3d, and C5b-9 in plasma of aABMR, and acute T-cell mediated rejection (aTCMR), and non-rejection kidney transplant recipients. Intra-renal complement markers were analyzed as C4d, C3d, C5b-9, and CD59 deposition. We examined in vitro complement activation and CD59 expression on renal endothelial cells upon incubation with human leukocyte antigen antibodies. Methods We included 50 kidney transplant recipients, who we histopathologically classified as aABMR (n=17), aTCMR (n=18), and non-rejection patients (n=15). Results Complement activation in plasma did not differ across groups. C3d and C4d deposition were discriminative for aABMR diagnosis. Particularly, C3d deposition was stronger in glomerular (P<0,01), and peritubular capillaries (P<0,05) comparing aABMR to aTCMR rejection and non-rejection biopsies. In contrast to C3d, C5b-9 was only mildly expressed across all groups. For C5b-9, no significant difference between aABMR and non-rejection biopsies regarding peritubular and glomerular C5b-9 deposition was evident. We replicated these findings in vitro using renal endothelial cells and found complement pathway activation with C4d and C3d, but without terminal C5b-9 deposition. Complement regulator CD59 was variably present in biopsies and constitutively expressed on renal endothelial cells in vitro. Conclusion Our results indicate that terminal complement might only play a minor role in late aABMR, possibly indicating the need to re-evaluate the applicability of terminal complement inhibitors as treatment for aABMR.